2011
DOI: 10.5301/ejo.2011.6403
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Characteristics, and Causes of Vision Loss in Patients with Ocular Toxoplasmosis

Abstract: Ocular toxoplasmosis is a common cause of uveitis. Our patients were more likely than general uveitis patients to be young, male, and Latino, often having emigrated from Mexico or Central or South America. The most common contributors to decreased vision in eyes with active lesions were inflammation and macular involvement, whereas in eyes with inactive lesions they were macular scar formation and amblyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 50 publications
(44 reference statements)
4
43
1
5
Order By: Relevance
“…24 Patients with OT are generally young adults, and in our study group, 76% of the patients were younger than 45 years. Similar results were found in other studies, 5,18,22,23,25 for instance, Bosch-Driessen et al 5 showed that the mean age at first presentation of OT was 29.5 years and that patients with primary ocular lesions were significantly older than those with combinations of active lesions and old scars. Also, Garweg et al 25 reported that the mean age at the first occurrence of OT was 23.9 years and patients with only one episode were older at first manifestation than those with two episodes (29.6 and 17.9 years, respectively).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…24 Patients with OT are generally young adults, and in our study group, 76% of the patients were younger than 45 years. Similar results were found in other studies, 5,18,22,23,25 for instance, Bosch-Driessen et al 5 showed that the mean age at first presentation of OT was 29.5 years and that patients with primary ocular lesions were significantly older than those with combinations of active lesions and old scars. Also, Garweg et al 25 reported that the mean age at the first occurrence of OT was 23.9 years and patients with only one episode were older at first manifestation than those with two episodes (29.6 and 17.9 years, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…Primary OT at first presentation has been reported at rates of 28-42.5%. 5,6,22,23 The greater frequency of recurrent disease may be accounted for by old peripheral lesions that go unnoticed by the patient; this is also supported by our clinical findings of a combination of active lesions and old retinochoroidal scars at a greater frequency than the patients were aware of.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations